Physico-chemical characterisation of material fractions in residual and source-segregated household waste in Denmark. (August 2016) - Götze, R.; Pivnenko, K.; Boldrin, A.; Scheutz, C.; Astrup, T. Fruergaard
Highlights: Dataset of 74 physico-chemical properties for 49 residual and 24 source-segregated fractions. Fractioning considered material recycling processes and function (i.e. packaging). Significant differences in properties of fractions in residual and source-segregated waste. Significant differences in properties of individual materials within fractions. Rare earth elements were detected in all fractions with highest concentrations in ceramics. Abstract: Physico-chemical waste composition data are paramount for the assessment and planning of waste management systems. However, the applicability of data is limited by the regional, temporal and technical scope of waste characterisation studies. As Danish and European legislation aims for higher recycling rates evaluation of source-segregation and recycling chains gain importance. This paper provides a consistent up-to-date dataset for 74 physico-chemical parameters in 49 material fractions from residual and 24 material fractions from source-segregated Danish household waste. Significant differences in the physico-chemical properties of residual and source-segregated waste fractions were found for many parameters related to organic matter, but also for elements of environmental concern. Considerable differences in potentially toxic metal concentrations between the individual recyclable fractions within one material type were observed. This indicates that careful planning and performance evaluation of recycling schemes are important to ensure a high quality of collected recyclables. Rare earth elements (REE) were quantified in all waste fractions analysed, with the highest concentrations of REE found in fractions with high content of mineral raw materials, soil materials and dust. The observed REE concentrations represent the background concentration level in non-hazardous waste materials that may serve as a reference point for future investigations related to hazardous waste management. The detailed dataset provided here can be used for assessments of waste management solutions in Denmark and for the evaluation of the quality of recyclable materials in waste.